Gender Mainstreaming Analysis of COVID-19 Vaccination Policy in Aceh: A Communication Perspective - Ade Irma; Aklima Aklima; Ramzi Murziqin; Chaidir Ali (Dirasah International Journal of Islamic Studies, 2025)
COVID-19 vaccination programs implemented under health emergency conditions risk reproducing gender inequities unless explicitly designed to accommodate the differentiated needs of men and women. This study examines Gender Mainstreaming (GM) in the implementation of COVID-19 vaccination services in Aceh Province, Indonesia, in 2021, with reference to Minister of Health Regulation No. 84 of 2020. The study aims to evaluate whether vaccination services were gender-responsive and to identify indicators of social inequality throughout the vaccination process. A concurrent mixed-methods design was employed, combining structured questionnaires, in-depth interviews, Focus Group Discussions, and documentary analysis. Data were collected from 320 respondents and 48 interviews across four sites — Banda Aceh City, Langsa City, Lhokseumawe City, and Bener Meriah Regency — and analyzed using the Gender Analysis Pathway (GAP) model across five dimensions: government commitment and policy, institutional framework, human resources, disaggregated data, and community participation. Findings indicate that COVID-19 vaccination in Aceh achieved an overall GM score of 85.84%, categorizing services as gender-sensitive and approaching gender-responsive. Nonetheless, indicators of social inequality were identified, particularly in the form of limited and uneven communication outreach, the absence of sex-disaggregated data presentation, and the reliance on administrative sanctions to mobilize participation rather than awareness-based approaches. These findings suggest that achieving genuinely gender-responsive health services requires not only regulatory compliance but also sustained capacity-building for field implementers and the adoption of equity-centered communication strategies at all levels of service delivery.